The clumsiest people in Europe : or, Mrs. Mortimer's bad-tempered guide to the Victorian world /: or, Mrs. Mortimer's bad-tempered guide to the Victorian world. (2006) - Mortimer, Favell Lee, 1802-1878
No abstract available